2004
DOI: 10.1007/978-3-540-24595-7_26
|View full text |Cite
|
Sign up to set email alerts
|

Planar Embeddings of Graphs with Specified Edge Lengths

Abstract: Abstract.We consider the problem of finding a planar embedding of a (planar) graph with a prescribed Euclidean length on every edge. There has been substantial previous work on the problem without the planarity restrictions, which has close connections to rigidity theory, and where it is easy to see that the problem is NP-hard. In contrast, we show that the problem is tractable-indeed, solvable in linear time on a real RAM-for planar embeddings of planar 3-connected triangulations, even if the outer face is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Strengthening earlier results by Whitesides [49] and Eades and Wormald [13], Cabello, Demaine, and Rote [7] showed that the plane realizability problem is (strongly) NP-hard even when restricted to 3-connected, infinitesimally rigid planar graphs with unit edge lengths. Plane realizable graphs with unit edge lengths-plane unit distance graphs-are known as matchstick graphs.…”
Section: Plane Realizations and Matchstick Graphsmentioning
confidence: 51%
See 1 more Smart Citation
“…Strengthening earlier results by Whitesides [49] and Eades and Wormald [13], Cabello, Demaine, and Rote [7] showed that the plane realizability problem is (strongly) NP-hard even when restricted to 3-connected, infinitesimally rigid planar graphs with unit edge lengths. Plane realizable graphs with unit edge lengths-plane unit distance graphs-are known as matchstick graphs.…”
Section: Plane Realizations and Matchstick Graphsmentioning
confidence: 51%
“…Realizability depends on the notion of drawing we use; in the standard definition of a drawing, different vertices cannot coincide in the drawing and a vertex cannot lie on an edge unless it is an endpoint of that edge. 7 If we do allow vertices to coincide and lie on edges, we enter the realm of linkages. For example, K 2,3 cannot be realized by a standard straight-line drawing in the plane if all edges have unit length, but it can be realized as a linkage with vertices overlapping.…”
Section: Realizability Of Graphsmentioning
confidence: 99%
“…In addition to the results on linear cartograms [3,5,12,18], several other papers are also related. Weights of edges (but for very different applications) can also be visualized by the width [2].…”
Section: Related Workmentioning
confidence: 99%
“…"Relative lengths" of stretches are immediately quantified, whereas "relative colors" do not have a clear interpretation. These observations have led to the development of linear cartograms [3,5,12,18]. Linear cartograms try to display time more clearly by distorting the base map.…”
Section: Introductionmentioning
confidence: 99%
“…For example, metro maps show connectivity of metro lines while abstracting from geographic reality (correct location) [11], and cartograms may show countries by using size (area) to depict total population [15]. Cartograms come in different types: contiguous area [7,9], non-contiguous area [12], rectangular [10], rectilinear [4], circle [6], and linear cartograms [5]. Except for the linear cartogram, all types use the area to show a variable of interest (often population).…”
Section: Introductionmentioning
confidence: 99%